Intubation during spinal motion restriction using the Lubo TM cervical collar a minikin simulation study - Behari, Dinell (Department of Anaesthesia and Perioperative Medicine, 2023)
Introduction: The Lubo TM collar is a cervical motion restriction device featuring a unique external jaw-thrust mechanism designed to provide non-invasive airway patency. In addition, tracheal intubation is facilitated by releasing an anterior chin strap; this allows better mouth opening than the previous generation of semi-rigid cervical collars. This study aimed to compare tracheal intubation using the Lubo TM collar combined with manual in-line stabilization (MILS) to intubation with MILS alone. The primary outcome was the time to successful intubation. Secondary outcomes compared intubation success rate, Cormack-Lehane grade, ease of intubation and dental trauma. Methods: A randomized, cross-over, equivalence study was performed. Eighty full-time physician anaesthesia providers were recruited. Participants performed tracheal intubation using direct laryngoscopy on a manikin under two different scenarios: with the Lubo TM collar and MILS applied, and with MILS and no cervical collar. The time to successful intubation was measured and compared using two-one-sided and paired t-tests. Results: Intubation times fell well within the a priori equivalence limits of 10 seconds, with a mean difference (95% CI) of 0.52 seconds (-1.30 to 2.56). There was no significant difference in intubation time with the Lubo TM collar (mean [SD] 19.2 [4.5] seconds) compared to the MILS alone group (19.7 [5.2] seconds). The overall success rate was 98.7% in the Lubo group and 100% in the MILS group. Adequate laryngoscopy views (Cormack-Lehane grades I to IIb) were equivalent between groups (Lubo 92.5% versus MILS alone 93.7%). Conclusion: In this manikin-based study, the time to intubation with the Lubo TM collar and MILS applied was equivalent to time to intubation with MILS alone, with similar intubating conditions. Thus, the Lubo TM collar and MILS may simplify airway management by reducing the number of steps required to perform intubation in patients requiring cervical motion restriction.